I’M ALWAYS ONLINE: PROBLEMATIC INTERNET USE AND RISK FACTORS IN ELEMENTARY SCHOOL STUDENTS - Nur Rahmawati, Ajeng Intan (Jurnal Psikologi, 2023)
This study aims to reveal the risk factors that cause Problematic Internet Use (PIU) in children. This surveyresearch used a cross sectional design by giving questionnaires Generalized Problematic Internet Use Scale 2(GPIUS2), Interpersonal Skill Competence, and Achievement Motivation Scale to 278 participants. Participantswere obtained using quota sampling with the criteria, namely, elementary school students aged 9-12 years. Theresearch subjects who were netted in the first phase are re-screened with the new inclusion criteria who wereidentified as having PIU with only moderate to very high hypothetical categories. As many as, 98 students whoexperienced PIU were obtained and were used as the final research subject. The results showed that as many as86 students or equivalent to 30.93% had fallen into the category of experiencing problematic internet usetendencies and as many as 12 students or equivalent to 4.31% were in the heavy category of dependence on theinternet (Internet Dependence). Besides that, Interpersonal skills and achievement motivation together wereshown to have a negative effect on PIU, t(97) = -1.45, p < .05, and t(97) = -1.58, p < .05, respectively. Based onthese results, counselors should be able to provide preventive and curative services, in order to maintain optimalgrowth and development in children.